Hypertension, Microvascular Pathology, and Prognosis After an Acute Myocardial Infarction. Issue 3 (September 2018) - Carrick, David; Haig, Caroline; Maznyczka, Annette M.; Carberry, Jaclyn; Mangion, Kenneth; Ahmed, Nadeem; Yue May, Vannesa Teng; McEntegart, Margaret; Petrie, Mark C.; Eteiba, Hany; Lindsay, Mitchell; Hood, Stuart; et al.
Abstract : The rationale for our study was to investigate the pathophysiology of microvascular injury in patients with acute ST-segment–elevation myocardial infarction in relation to a history of hypertension. We undertook a cohort study using invasive and noninvasive measures of microvascular injury, cardiac magnetic resonance imaging at 2 days and 6 months, and assessed health outcomes in the longer term. Three hundred twenty-four patients with acute myocardial infarction (mean age, 59 [12] years; blood pressure, 135 [25] / 79 [14] mm Hg; 237 [73%] male, 105 [32%] with antecedent hypertension) were prospectively enrolled during emergency percutaneous coronary intervention. Compared with patients without antecedent hypertension, patients with hypertension were older (63 [12] years versus 57 [11] years; P <0.001) and a lower proportion were cigarette smokers (52 [50%] versus 144 [66%]; P =0.007). Coronary blood flow, microvascular resistance within the culprit artery, infarct pathologies, inflammation (C-reactive protein and interleukin-6) were not associated with hypertension. Compared with patients without antecedent hypertension, patients with hypertension had less improvement in left ventricular ejection fraction at 6 months from baseline (5.3 [8.2]% versus 7.4 [7.6]%; P =0.040). Antecedent hypertension was a multivariable associate of incident myocardial hemorrhage 2-day post-MI (1.81 [0.98–3.34]; P =0.059) and all-cause death or heart failure (n=47 events, n=24 with hypertension; 2.53 [1.28–4.98]; P =0.007) postdischarge (median follow-up 4 years). Severe progressive microvascular injury is implicated in the pathophysiology and prognosis of patients with a history of hypertension and acute myocardial infarction. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02072850. Abstract : Supplemental Digital Content is available in the text.